Isolates of Septoria glycines , Causal Agent of Brown Spot of Soybean, in North Dakota Contain the G143A Mutation Conferring Resistance to Quinone Outside Inhibitor Fungicides - Danilo L. Neves; Brandt G. Berghuis; Jessica M. Scherer; Bryan C. Hansen; Samuel G. Markell; Carl A. Bradley (Plant Health Progress, 2026)
Brown spot of soybean ( Glycine max) caused by Septoria glycines is a commonly observed foliar disease that has been managed with the application of fungicide products that contain quinone outside inhibitor (QoI) active ingredients. Isolates of S. glycines obtained from North Dakota soybean fields in 2020 were tested for their sensitivity to QoI fungicides using a discriminatory dose assay and a molecular assay. From these assays, 3 out of 30 S. glycines isolates were resistant to QoI fungicides conferred by the G143A mutation. In light of these findings, North Dakota soybean growers should be made aware that if fungicide application is warranted for management of brown spot in the future, active ingredients alternative to the QoI group may be necessary to achieve satisfactory efficacy. [Formula: see text] Copyright © 2026 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .